مقارنة تأثير معقد النحاس (II) الجديد والمستخلص المائي لنبات المردقوش Origanum Vulgare L. مع عقار السايكلوفوسفومايد على نمو الخط الخلوي L20B. - مرتضى جنان حسين (Al-Nahrain Journal of Science)
Line L20B The origanum vulgare L. plant which used as a medical plants for treatment of chest and bronchial inflammation and others. The copper complex (II) regarded as a. chemical treatments which used as anti-cancer therapy by its cytotoxic effect towards cancer cell line and the percentage of inhibition. This study involoved effect of the active compounds for the aqueous extract of the origanum vulgare L. and effect of a new copper(II)complex on cell comparison with cytotoxic drug cyclophosphamide (cp) positive control, through employed in vitro system by study of inhibition percentage rate on murine cell line L20B derived from mouse cell (fibroblasts), Using four concentrations (31.25,62.5,125,250) microgram/ ml within two exposure time (48,72) hours. The results showed that increased of inhibition percentage a according to concentration with significant difference (p< 0.05) for both aqueous extract plant and copper (II) complex comparison with cyclophosphamide (cp) and there is no effect of time exposure on inhibition percentage. We conclude from this study that effect of aqueous origanum vulgare extract and copper (II) complex similar to effect of cytotoxic drug (cp) and there is no significant difference between them at all concentrations. The inhibition levels reached to 52.41%, 58.21% and 58.93% respectively at 250µg/ml after 72 hour exposure time.